ANALISIS PERANG HIBRIDA RUSIA TERHADAP UKRAINA DI KRIMEA TAHUN 2014 - Ramadhan, Naufalariq Rizqi; Putri, Penny Kurnia; Resen, Putu Titah Kawitri (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This study aimed at analyzing the factors that influenced Russia in carrying out a hybrid war in Crimea in 2014, using descriptive qualitative research methods with data sources obtained through literature studies. The suspension of cooperation in the European Association Agreement between Ukraine and the European Union sparked an uprising, Russia took advantage of the situation to retake Crimea. Due to Ukraine's proximity to the West, Russia has implemented hybrid warfare in carrying out its actions. In analyzing this case, the researcher uses strategic theory and the concept of national security. The researcher finds the factors that influence Russia to carry out a hybrid war, including: Russia's desire to control the Black Sea Fleet, Russia wants to show its massive economic influence on the West, Ukraine is a buffer zone for Russia, and Russia wants to protect Russian citizens and Russian-speakers in Crimea. Keywords: Crimea, Hybrid War, National Security, Russia-Ukraine